2021
DOI: 10.1186/s12879-020-05747-4
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characteristics of HBV infection among blood donors tested HBsAg reactive in a single ELISA test in southern China

Abstract: Background Hepatitis B virus (HBV) infection is a major concern for blood safety in high-prevalence HBV countries such as China. In Shenzhen, dual hepatitis B surface antigen (HBsAg) enzyme-linked immunosorbent assays (ELISAs) have been adopted in parallel with nucleic acid testing (NAT) for donors for over a decade. A small proportion of blood donors test reactive (R) for HBsAg but negative through routine NAT, which can lead to HBV infection with an extremely low viral load. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 22 publications
1
1
0
Order By: Relevance
“…An American comprehensive study from 22.4 million blood donors screened by HBsAg, anti-HBc, and NAT also revealed that only 43/404 (10.6%) OBIs could be detected by MP-NAT, while most of OBIs (361/404, 89.4%) with low viral loads could only be identi ed by ID-NAT[24]. This conclusion was consistent with another previous study which reported HBV MP NAT failed to detect approximately 92% (46 of 593) of OBI donors[25]. Out of 103,356 seronegative Chinese blood donations, Fifty-six out of 98 reactive MPs (57.1%) were resolved as HBV DNA+, but 17 non-resolved donations identi ed as OBIs by alternative NAT assays were missed by MP-NAT[12].…”
supporting
confidence: 89%
“…An American comprehensive study from 22.4 million blood donors screened by HBsAg, anti-HBc, and NAT also revealed that only 43/404 (10.6%) OBIs could be detected by MP-NAT, while most of OBIs (361/404, 89.4%) with low viral loads could only be identi ed by ID-NAT[24]. This conclusion was consistent with another previous study which reported HBV MP NAT failed to detect approximately 92% (46 of 593) of OBI donors[25]. Out of 103,356 seronegative Chinese blood donations, Fifty-six out of 98 reactive MPs (57.1%) were resolved as HBV DNA+, but 17 non-resolved donations identi ed as OBIs by alternative NAT assays were missed by MP-NAT[12].…”
supporting
confidence: 89%
“…Thus, it is not suitable for popularization in a resource-limited area ( Weber et al, 2019 ). Another method, enzyme-linked immunosorbent assay (ELISA) usually takes 1∼2 days to get the detection result, and the antibody preparation cycle is long ( Ye et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%